2004
DOI: 10.1111/j.1365-3091.2004.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Supply limited sediment transport in a high‐discharge event of the tropical Burdekin River, North Queensland, Australia

Abstract: Interactions between catchment variables and sediment transport processes in rivers are complex, and sediment transport behaviour during high‐flow events is not well documented. This paper presents an investigation into sediment transport processes in a short‐duration, high‐discharge event in the Burdekin River, a large sand‐ and gravel‐bed river in the monsoon‐ and cyclone‐influenced, semi‐arid tropics of north Queensland. The Burdekin's discharge is highly variable and strongly seasonal, with a recorded maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 28 publications
3
61
0
Order By: Relevance
“…Linking SSC to a hydraulic parameter using a rating curve mostly results in a large scatter of observations around the rating curve (Al-Ansari et al, 1988;Amos et al, 2004;Bogen, 2004). Also, the Q -SSC relation often shows considerable hysteresis effects (Asselman, 1847(Asselman, 1997Picouet et al, 2001;Morehead et al, 2003;Bogen, 2004).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Linking SSC to a hydraulic parameter using a rating curve mostly results in a large scatter of observations around the rating curve (Al-Ansari et al, 1988;Amos et al, 2004;Bogen, 2004). Also, the Q -SSC relation often shows considerable hysteresis effects (Asselman, 1847(Asselman, 1997Picouet et al, 2001;Morehead et al, 2003;Bogen, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Predicting SSC from Q using a rating curve, therefore, generally results in poor predictions of SSC in the course of flood events, and may even result in poor estimates of annual budgets. It has been widely recognized that SSC is controlled by the amounts of sediment supplied from upstream parts of a catchment, and by the timing of suspended sediment supply from different tributaries to the lower reaches in larger river basins ( (Bogen 1980;Webb, 1981, 1982;Spott and Guhr, 1994;Asselman, 1997;Morehead et al, 2003;Amos et al, 2004;Moliere et al, 2004). Exhaustion of sediment supply from the upstream basin is generally seen as a major cause of clockwise hysteresis in the Q -SSC relation (Asselman, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…These parameters can modify the effect of sediment on aquatic ecosystems (Culp et al, 1986;Carvalho, 1994;Francoeur & Biggs, 2006). High sediment loads are associated with high discharge events, and some studies found a linear relationship between flow and suspended sediment concentration (Amos et al, 2004). High flows during spates, and the associated increase in sediment transport, usually reduce density of benthic organisms (Melo et al, 2003a;Bond & Downes, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Transport of sediment is dependent upon hydraulic parameters, such as flow, streambed slope, and the local bed composition (Wood & Armitage 1997;Amos et al, 2004). These parameters can modify the effect of sediment on aquatic ecosystems (Culp et al, 1986;Carvalho, 1994;Francoeur & Biggs, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Discharge events, caused by monsoon rain or tropical cyclones, rise rapidly to a peak up to three orders of magnitude larger than base flow and then decline almost as quickly (Alexander et al 1999;Amos et al 2004). …”
Section: Bottomset Formation In the Modern Burdekin Rivermentioning
confidence: 99%